Potential application of LDPE plastic waste 45 into tiles - Awang, Zarizi; M. Yusof, Nuur Asyikin; Tajul Baharuddin, Mohamad Faizal; Hashim, Nor Haslina; Mohd Arish, Nur Aini; Abdul Rahman, Mohd Fahmi (Penerbit UTHM, 2020)
Plastic has interesting characteristics which makes it the most used material in the world. However, plastic is known to be a non-biodegradable material which unable to naturally decompost in soil and thus contribute to environmental issue. As alternative, plastic waste has been recycled to produce quality and sustainable construction materials as the source is abundant. Thus, this study is carried out to utilize plastic waste particularly low density polyethylene (LDPE) and with sand in manufacturing tiles in two different sand and plastic waste ratios of 2:1 and 2:2. The tiles manufactured were further analyzed for their water absorption and compressive strength. It was found that the tiles made of mixture ratio of 2:2 have higher compressive strength and lower weight compared to that of 2:1 ratio. The average weight of tiles for 2:1 ratio was 891.59 g, while ratio 2:2 produced tiles with weight of 1319.5 g. Tiles manufactured from the plastic waste also showed better water absorption and compressive strength compared to normal cement tiles.